Obiectul material sau imaterial al infracțiunilor de luare de mită și de dare de mită: considerații introductive [Articol] - Brînza, Cristian (CEP USM, 2021)
In art. 333 of the Criminal Code, the content of the material or immaterial object of the offense is described by the phrase “goods, services, privileges or advantages in any form, which are not due, [...] offers or promises.” In art. 334 of the Criminal Code, the content of the material or immaterial object of the offense is described by the phrase “goods, services, privileges or advantages in any form, which are not due to him”. The licit remuneration is the corporal or incorporeal entity in connection with which the social relations appear and develop, in which the bribed person and the briber participate as subjects. Committing the offenses provided in art. 333 and 334 of the Criminal Code, these subjects make it impossible to develop the respective social relations or complicate their development. The result of the work thus performed derives directly from the undue service or advantage, not from the values and social relations defended against bribery and bribery. A service act cannot represent the immaterial or immaterial object of the offenses provided in art. 333 and 334 of the Criminal Code.
Keywords: mita; taking bribes; giving bribes